(untitled) (Revista de Investigaciones Universidad del Quindío, 2010)
A method of storage for conservation of Genipa americana seeds was evaluated. Seeds were from 6 populations located in the entire warm area of Quindio. The study was conducted in the laboratory of Biotechnology, Centre for Studies and Research on Biodiversity and Biotechnology at the University of Quindio (CIBUQ). A methodology suggested by Bioversity International for handling seeds in gene banks was used in order to establishing a storage protocol for short-term conservation of seeds of the species through the determination of temperature and substrate proper to storage. Initial tests revealed 75% viability, 43% moisture content, 78% germination percentage, germination speed index of 2 seeds per day and 23 days for germination rate. The potential of germination of Genipa americana can keep itself to short-term in storage at room temperature, using torlita to control the moisture content which should be only up to 10% for keeping its viability. The results obtained show that the storage behavior of Genipa americana seeds is similar to any type of intermediate seed.